A New Open-framework Iron Borophosphate from Ionic Liquids: KFe[BP2O8(OH)] - Guangmei Wang; Anja-Verena Mudring (Crystals, 2011)
A new open-framework iron borophosphate, KFe[BP2O8(OH)], has been obtained by ionothermal synthesis from KH2PO4, FeCl3∙4H2O, H3BO3 and [C4mpyr]Br (1-butyl-1-methylpyrrolidinium bromide). Single-crystal X-ray diffraction analysis shows that KFe[BP2O8(OH)] (monoclinic, P21/c, a = 9.372(2) Å , b = 8.146(2)Å , c = 9.587(2) Å, β = 101.18(3)°, V = 718.0(2)Å3 and Z = 4) has a three-dimensional (3-D) framework structure composed by {Fe(III)O5(OH)} octahedra as well as {BO3(OH)} and PO4 tetrahedra. As anionic structural sub-unit, KFe[BP2O8(OH)], contains an infinite open-branched {[BP2O8(OH)]4-} chain which is formed by alternating {BO3(OH)} and PO4 tetrahedra. {Fe(III)O5(OH)} octahedra share common O corners with five phosphate tetrahedra and the OH corner links to the hydrogen borate group to give a 3D framework. The negative charges of the inorganic framework are balanced by K+ ions.